Lower risk of dementia with AS01-adjuvanted vaccination against shingles and respiratory syncytial virus infections - Maxime Taquet; John A. Todd; Paul J. Harrison (npj Vaccines)
Abstract AS01-adjuvanted shingles (herpes zoster) vaccination is associated with a lower risk of dementia, but the underlying mechanisms are unclear. In propensity-score matched cohort studies with 436,788 individuals, both the AS01-adjuvanted shingles and respiratory syncytial virus (RSV) vaccines, individually or combined, were associated with reduced 18-month risk of dementia. No difference was observed between the two AS01-adjuvanted vaccines, suggesting that the AS01 adjuvant itself plays a direct role in lowering dementia risk.